NURETTA DEVIANA: CHILDREN BEHAVIORAL SHAPING MELALUI PEMBELAJARAN BAHASA INGGRIS BERBASIS AKULTURASI BUDAYA BAGI SISWA SEKOLAH DASAR - Eko Heriyanto; Adhitya Wisnumurti; Adityo Putro Wicaksono (Universitas Aki, 2020)
English has become part of the education curriculum that must be taught to students. Therefore, many schools strive to provide the best English teaching and learning systems and methods for their students. One of them is Nuretta Deviana which is an alternative model of learning English. The purpose of this research is to explain the steps of implementing Nuretta Deviana, find and explain the skills and language components that can be learned through Nuretta Deviana, explain the children behavioral forming through NUretta Deviana, find and overcome the obstacles that arise in the implementation of Nuretta Deviana. The approach used is descriptive qualitative based on literature review. Primary data were collected using documentation techniques during the Nuretta Deviana process, performances, and interviews with stakeholders and educators (English teachers in schools). Secondary data were collected using the literature review method. The results of this study stated that Nuretta Deviana can be done by holding preparations, performances and assessments. Nuretta Deviana can hone student’ English skills and components. Diligent, hard work, discipline and tolerance characteristic are implicitly formed through the script which acculturate local culture and British culture. Barriers internally and externally can be overcome with solutions that are carried out continuously. Keywords: nursery rhymes, reader response theory